Drying Characteristics And Quality Attributes Of Black Tea Under Superheated Steam Drying - Nordin, Rumaisa (2019)
The balanced flavour of black tea can be achieved from its tea leaves drying process. However, conventional dryers used in the current tea industries consume a large amount of thermal energy that comes from firewoods as their primary source of heat. This eventually raises concerns on the environmental impacts of firewood usage. Superheated steam dryer (SSD) is an advanced drying technology that utilises steam as the heating medium. The impact of SSD on the black tea drying process is still limited in terms of understanding the drying characteristics and mechanisms, quality attributes, and energy consumption. Therefore, this study aims to explore the capability of SSD as a practical option for tea drying. Firstly, the effect of SSD temperature range (120–200ºC) on black tea drying characteristics was investigated.